Development of power through plyometrics and its impact onreactive strength in youth football players in the Valle de losChillos league - Tapia Bonilla , Johanna Noemi; Vargas Guerrero , Juan Javier; Sanmartín Cruz , Hamilto Daniel (SATHIRI, 2024)
Reactive strength training allows the player to make sudden changes of direction with the control of the ball, and therefore get as close as possible to the goal where they must place the ball as a goal. In this sense, the enhancement of this physical capacity is vital for the sustained increase of sports performance in footballers. Therefore, the objective of the research is to enhance the reactive strength in youth soccer players of the Valle de los Chillos from the application of plyometric exercises. Based on purposive sampling, the research will select the total study population of the Valle de los Chillos League soccer team (25 athletes), Youth category (17.5 years), male, also involving in the research three coaches who participate in their process of directing sports training. Once the initial diagnosis of the research was made, several plyometric exercises were implemented in three phases. Three tests were applied to assess sports performance related to reactive strength (non-impulse jump, vertical jump, and ball marking and control) at two times. The comparison of the data obtained at two points in the aforementioned tests showed significant improvements in favor of the posttest, demonstrating a notable improvement in the physical capacity of reactive strength, fulfilling the objective of the research.